2005
DOI: 10.1121/1.1906060
|View full text |Cite
|
Sign up to set email alerts
|

Perception of familiar contrasts in unfamiliar positions

Abstract: This paper investigates the perception of non-native phoneme contrasts which exist in the native language, but not in the position tested. Like English, Dutch contrasts voiced and voiceless obstruents. Unlike English, Dutch allows only voiceless obstruents in word-final position. Dutch and English listeners' accuracy on English final voicing contrasts and their use of preceding vowel duration as a voicing cue were tested. The phonetic structure of Dutch should provide the necessary experience for a native-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 22 publications
2
54
0
Order By: Relevance
“…For Dutch listeners in Experiment 1a, Dutchaccented /ekt/ and /mu:f/ were perceptually closer to the correct English pronunciation than Japanese-accented primes were. Note however, that Dutch listeners are less likely to confuse English /e/ with /ae/ than they are to confuse /ae/ with /e/ , and they can categorize English final voicing contrasts as accurately as native English listeners can (Broersma, 2005(Broersma, , 2008(Broersma, , 2010; they just seem to be less good at using this information for online word recognition (e.g., Broersma & Cutler, 2008;Cutler et al, 2006;). While we do not want to claim that perceptual difficulties did not modulate the results in Experiment 1a, it is simply not possible to tease apart the influence of perceptual confusions from experiential effects for Dutch-accented primes and Dutch listeners.…”
Section: Experiments 1bmentioning
confidence: 99%
See 1 more Smart Citation
“…For Dutch listeners in Experiment 1a, Dutchaccented /ekt/ and /mu:f/ were perceptually closer to the correct English pronunciation than Japanese-accented primes were. Note however, that Dutch listeners are less likely to confuse English /e/ with /ae/ than they are to confuse /ae/ with /e/ , and they can categorize English final voicing contrasts as accurately as native English listeners can (Broersma, 2005(Broersma, , 2008(Broersma, , 2010; they just seem to be less good at using this information for online word recognition (e.g., Broersma & Cutler, 2008;Cutler et al, 2006;). While we do not want to claim that perceptual difficulties did not modulate the results in Experiment 1a, it is simply not possible to tease apart the influence of perceptual confusions from experiential effects for Dutch-accented primes and Dutch listeners.…”
Section: Experiments 1bmentioning
confidence: 99%
“…For Dutch-accented primes, the vowel /ae/ was replaced with /e/ in Vowel items (act pronounced as /ekt/), and the wordfinal /v/ was replaced with /f/ in Consonant items (move pronounced as /mu:f/). Dutch lacks the vowel /ae/ in its phoneme inventory (e.g., Gussenhoven, 1999), and it is well known that Dutch learners of English tend to perceive and produce English /ae/ as /e/, a vowel that also exists in Dutch (Broersma, 2005;Cutler & Broersma, 2005;Cutler, Weber, Smits, & Cooper, 2004;Schouten, 1975;Tops et al, 2001;. Similarly, the entire class of word-final obstruents gets devoiced in Dutch, and Dutch learners characteristically devoice final obstruents also in English (Tops et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, even though Dutch listeners correctly perceive both /ae/ and /e/ in English as front vowels, they only access entries containing orthographic 'e' because they constitute their only lexical match for their perception (as words containing orthographic 'a' can only be accessed if a back vowel is perceived). Some evidence suggests that this hypothesis is plausible: Perception studies that have indicated a bias towards /e/ in Dutch learners' perception of English (Broersma, 2005; have used materials that included orthographic representations of words, such as 'bet' or 'bat', to measure Dutch listeners' classification of English syllables or words containing /ae/ and /e/.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, native speakers of Japanese have difficulty distinguishing the English words rocket and locket (Aoyama, Flege, Guion, Akahane-Yamada, & Yamada, 2004), while native speakers of Spanish (Flege, Bohn, & Jang, 1997) and Portuguese (Bion, Escudero, Rauber, & Baptista, 2006;Rauber, Escudero, Bion, & Baptista, 2005) have difficulty distinguishing the English words beat and bit, and native speakers of Dutch have difficulty with the English words bet and bat (Broersma, 2005;Cutler & Broersma, 2005). A common characteristic among these pairs of words is that they are differentiated by L2 contrasts which do not have immediate counterparts in the learners' native languages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation